2017
DOI: 10.1111/coa.12827
|View full text |Cite
|
Sign up to set email alerts
|

Local extension staging of sinonasal tumours: retrospective comparison between CT/MRI assessment and pathological findings

Abstract: Systematic pathologic analysis of the anatomical areas around the sinonasal cancer has to be applied in further studies to improve our therapeutic management. CT/MRI mapping cannot replace accurate assessment of tumour extension during surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The shortcomings of these classifications may be due to their initial description based on a small number of patients, patients without an MRI or at a time when an MRI was too recent to allow accurate staging of intracranial or intraorbital extension. Even with CT and MRI, accurate staging remains difficult . Jankowski et al recently proposed a new prognostic classification based on the behavior of ONB inside and outside the olfactory cleft, which still remains to be validated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shortcomings of these classifications may be due to their initial description based on a small number of patients, patients without an MRI or at a time when an MRI was too recent to allow accurate staging of intracranial or intraorbital extension. Even with CT and MRI, accurate staging remains difficult . Jankowski et al recently proposed a new prognostic classification based on the behavior of ONB inside and outside the olfactory cleft, which still remains to be validated.…”
Section: Discussionmentioning
confidence: 99%
“…Even with CT and MRI, accurate staging remains difficult. 23,24 Jankowski et al 25 recently proposed a new prognostic classification based on the behavior of ONB inside and outside the olfactory cleft, which still remains to be validated. In the metaanalysis by Fu et al, 15 as in our study, the Hyams grade was not correlated with OS, DFS, or tumor status.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, few studies have examined the relationship between pathological spread and diagnostic images in SBTs. Mortuaire et al suggested that CT/magnetic resonance imaging (MRI) mapping cannot replace the accurate assessment of pathological tumor extension during surgery in sinonasal malignancies 4 . Although Bier et al described the low occurrence of false positives of dural enhancement by eMRI in carcinomatous meningeosis, 5 no conclusion has been reached about the accuracy of the pathological progression and CT/MRI findings in SBTs.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that a number of studies have reported significant discrepancies between clinical and pathological T categorization. 52,53 In particular, imaging is not sufficiently accurate in the assessment of invasion of the orbit, the skull base, and frontal or sphenoid sinuses. 52 Thus, careful histopathologic assessment is essential for a correct staging of sinonasal carcinomas.…”
mentioning
confidence: 99%
“…52,53 In particular, imaging is not sufficiently accurate in the assessment of invasion of the orbit, the skull base, and frontal or sphenoid sinuses. 52 Thus, careful histopathologic assessment is essential for a correct staging of sinonasal carcinomas. Finally, when neck lymph node dissections are included as part of the surgical specimen, a separate linked data set for Nodal Excisions and Neck Dissection Specimens for Head & Neck Tumours has to be completed.…”
mentioning
confidence: 99%